Flexible identity federation through centralized policy enforcement points XML gateways to the rescue. - Lascelles, Francois
Imagine a fresh business relationship between ACME Corporation and Partner. As a result of this relationship, ACME wants to grant Partner limited access to one of its core internal applications. They do this, naturally by exposing a Web service.